2020
DOI: 10.3389/fphys.2020.00373
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling and Monitoring of Training Distress and Illness in University Swimmers During a 25-Week Competitive Season

Abstract: Purpose: To evaluate relationships of proteomics data, athlete-reported illness, athlete training distress (TDS), and coaches' ratings of distress and performance over the course of the competitive season.Methods: Thirty-five NCAA Division II swimmers were recruited to the study (male n = 19, female n = 16; age 19.1 ± 1.6 years). Athletes provided fingerprick dried blood spot (DBS) samples, illness symptoms, and TDS every Monday for 19 of 25 weeks in their season. Coaches monitored performance and rated visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(57 reference statements)
0
9
0
Order By: Relevance
“… 126 DBS samples offer many advantages in the athletic and military settings, including ease and safety of transport and handling. 127 , 128 , 129 Proteins in the DBS samples are stable for long time periods at ambient conditions and can be eluted in solvents for later proteomics analysis.…”
Section: Multi-omics and Systemwide Approachesmentioning
confidence: 99%
“… 126 DBS samples offer many advantages in the athletic and military settings, including ease and safety of transport and handling. 127 , 128 , 129 Proteins in the DBS samples are stable for long time periods at ambient conditions and can be eluted in solvents for later proteomics analysis.…”
Section: Multi-omics and Systemwide Approachesmentioning
confidence: 99%
“…This pilot study has shown utility for one target blood-borne biomarker associated with the OR/OTS in Olympic athletes. Proteomic studies utilizing DBS tissue handling are purported in the field mainly linked to immune response and acute phase proteins in OR/ORTS [ 5 , 15 ]. The limitations of this study (sample size and homogeneity) reinforce the need for further germane field-based DBS data whilst controlling the likely confounding effect of serum capillary blood and the “matrix effect”.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these targeted analyses, shotgun proteomic analyses of DBS are still in their infancy [41]. As of now, only a few reports have been published on proteomic profiling from DBS [42,20,43,44]. Most of the above-mentioned methods (targeted and shotgun proteomic profiling) rely on a bottomup approach using the time-consuming trypsinization.…”
Section: Introductionmentioning
confidence: 99%